Introductory plant biology - Stern, Kingsley R. (McGraw-Hill Higher Education, 2008)
The book consists of 25 chapters covering all botanical subject The chapters deal with structure and function of botany, meiosis and genetics, plant propagation and biotechnology, evolution, botanical classification, stress in phylogenetic sequence, the diversity of organisms traditionally regarded as plants and ethonobotanical aspects